Peran Guru Pendidikan Agama Islam dalam Menerapkan Pendidikan Multikultural terhadap Pengembangan Sikap Toleransi Siswa di SMP Negeri 1 Ngoro Jombang - Solekha, Siti Latifatus; Huda, Saihul Atho' Alaul; Waslah, Waslah (Lembaga Yasin AlSys, 2025)
This study aims to analyze the role of Islamic Education (PAI) teachers in implementing multicultural education to develop students' tolerance at SMP Negeri 1 Ngoro Jombang. This research utilizes a descriptive qualitative method, with data collection techniques including observation, interviews, and documentation. The findings of this research indicate that Islamic Education teachers play a significant role in creating an inclusive learning environment that embraces diversity. Their roles include acting as guides, facilitators, and educators in the process of multicultural education. Islamic Education teachers at SMP Negeri 1 Ngoro Jombang successfully integrate values of tolerance, mutual respect between religions, and cultural diversity into the learning process. Moreover, these teachers serve as role models for students in fostering moderation and harmony among different religious groups. However, the study also identifies several external factors that support the implementation of multicultural education, such as school policies promoting diversity, the school's commitment to inclusivity, parental and community support, and collaboration between educators and school staff. A harmonious school environment also helps create a conducive learning atmosphere. On the other hand, external obstacles include a lack of parental awareness about the importance of multicultural education, insufficient teacher training in multiculturalism, and limited resources and learning media. Additionally, internal factors that support the implementation include the competence and professionalism of Islamic Education teachers, creativity in collaborative teaching, and active collaboration between subject teachers. Internal challenges identified include a lack of training and understanding related to multiculturalism, as well as limited facilities and learning resources.